Supplementation with spray-dried porcine plasma in piglets at birth: effects on protein metabolism and performance - Vicari Junior, Dirceu (2020)
This research was designed to evaluate whether supplementation of piglets with spray dried porcine plasma (SDPP) on the day of birth, have positive effect on protein metabolism and weight gain (WG) in suckling piglets, as well as on performance at the nursery phase. We selected 30 litters from gilts of at least one pair of piglets for each treatment, TA= control without SDPP, TB= oral administration of 10 g of SDPP, and TC= 20 g of SDPP. At birth, the piglets were weighed, identified and randomly distributed. Body weights were also measured on days 7, 14 and 19. Blood samples were collected to measure the level of urea, total protein (TP), albumin (AB) and globulin (GB). At weaning, 70 piglets from each treatment were distributed in five groups (replicates) of 14 piglets (seven males and seven females). Weights (animals and feed intake) were taken at post-weaning and at each feed change (days 14, 28 and 42 of raising). During the first two weeks of lactation, there were no effects of the treatments for the all evaluated variables. In the third week, TC piglets had higher serum levels of TP and GB, but lower WG than did control piglets. There was no effect of treatments on WG during the entire suckling period. There were no residual effects on nursery phase performance; however, treated piglets had less need for medications. SDPP supplementation did not influence zootechnical performance in the first two weeks or during the entire suckling period. The TC group had higher globulin levels than did the TA group. In the weaning phase, there were no effects on performance; however, there was a higher incidence of diseased animals in the TA group.